Maturation of the middle phalanx of the third finger and cervical vertebrae: a comparative and diagnostic agreement study. (17th September 2014) - Perinetti, G.; Perillo, L.; Franchi, L.; Di Lenarda, R.; Contardo, L.
Structured Abstract Objective Diagnostic agreement on individual basis between the third middle phalanx maturation (MPM) method and the cervical vertebral maturation (CVM) method has conjecturally been based mainly on overall correlation analyses. Herein, the true agreement between methods according to stage and sex has been evaluated through a comprehensive diagnostic performance analysis. Subjects and methods Four hundred and fifty‐one Caucasian subjects were included in the study, 231 females and 220 males (mean age, 12.2 ± 2.5 years; range, 7.0–17.9 years). The X‐rays of the middle phalanx of the third finger and the lateral cephalograms were examined for staging by blinded operators, blinded for MPM stages and subjects' age. The MPM and CVM methods based on six stages, two pre‐pubertal (1 and 2), two pubertal (3 and 4), and two post‐pubertal (5 and 6), were considered. Specifically, for each MPM stage, the diagnostic performance in the identification of the corresponding CVM stage was described by Bayesian statistics. Results For both sexes, overall agreement was 77.6%. Most of the disagreement was due to 1 stage apart. Slight disagreement was seen for the stages 5 and 6, where the third middle phalanx shows an earlier maturation. Conclusions The two maturational methods show an overall satisfactorily diagnostic agreement. However, at post‐pubertal stages, the middle phalanx of the third finger appears to mature earlier than the cervical vertebrae. Post‐pubertal growth phase should thus be based on the presence of stage 6 in MPM.